Periodontitis with Stage III, Grade C. Case report - Domínguez Gaibor, Denny (2020)
Periodontal disease affects patients’ health compromising the shape, function and aesthetics of the entirestomatognathic system, leading to significant deterioration in the quality of life of the patient. Using the actualclassification, we will evaluate the stages of disease of the periodontium depending on the severity,complexity of treatment and degrees according to the level of risk that the patient may present with. Thisclinical case proposes a comprehensive treatment of a 58-year-old male patient with periodontitisaccompanied by the new classification of periodontal diseases to make an adequate diagnosis, based onupdated scientific evidence. Both clinical and radiological assessments were performed as well asmeasurements of the depth of periodontal pockets using the WHO periodontal probe. These were recordedin the periodontogram to determine the pathology and staging of disease (Stage III, Grade C according toWorld Workshop), also taking into account the patient’s tobacco and coffee addiction. The treatment planconsists of different phases: Systemic phase, hygienic phase, corrective phase and maintenance phase. Theamount of cigarettes the patient consumed per day affected the treatment, despite the advice about theharmful effects of smoking. However, the depths of periodontal pockets were reduced and the patient’s oralhygiene improved.